The use of lacZ gene fusions in Neurospora crassa - M. S. SACHS; D. EBBOLE (Fungal Genetics Reports, 1990)
Systematic analyses of gene expression in diverse organisms have relied on genetic fusions in which the regulated expression of the product of the Escherichia coli lacZ gene, ß-galactosidase, is used to assay gene activity. Because there are low but readily detectable levels of ß-galactosidase in Neurospora crassa (e.g. Landman, Arch. Biochem. Biophys. 52:93-109, 1954), the use of E. coli lacZ as a reporter gene in this organism has not been extensively investigated. Here we report that lacZ fusion proteins can be used to analyze the regulation of two N. crassa genes, arg-2 and con-10. The levels of ß-galactosidase produced by strains carrying the fused genes indicate that they are developmentally regulated in a manner similar to the intact genes (Davis, Microbiol. Rev. 50: 280-313, 1986; Orbach, Sachs, and Yanofsky, J. Biol. Chem. in press 1990; Roberts, Berlin, Hager and Yanofsky, Mol. Cell. Biol. 8:2411-2418, 1988; Sachs and Yanofsky, in preparation).